PERILAKU MEKANIK TARIK BAMBU DAN POTENSI APLIKASINYA SEBAGAI PERKUATAN TANAH PADA TIMBUNAN - Suwartanti Suwartanti (Universitas Negeri Yogyakarta, 2005)
ABSTRACTThe main obstacle in building a construction in soft soil is the big settlementwhich occurs in such soil. One of the techniques to solve this problem is tohamper geosynthetics on this soft soil and create a compacted embankmentfrom good soil above the soft soil. The application of this technique is quiteeffective, but due to economic problem and environmental awareness, the useof another material which is cheaper and comes from nature is in urgent need.In the past our ancestors have used bamboo as soil reinforcement. Unfortunatelythe publications and researches concerning this matter are still very few.This study is aimed to investigate the tensile strength of woven bambooand its potential application for soil reinforcement in an embankment. Threevariants of bamboos are used in the experiment. The samples are taken fromthe outer parts (skin) and inner parts, with and without nodes. The shape anddimension of the samples are designed to represent the actual shape anddimension of woven bamboo.From the experiment, the maximum tensile strength obtained from tensilestrength and strain analysis is 395.533 kN/m'. The outer part of bamboo iscategorized as brittle material while the inner part is ductile. Based on thesefindings and considering bamboo's rough surface and its lifetime, bamboo ispotential for soil reinforcement in an embankment to replace a particular functionof geosynthetics.Keywords: bamboo, soil reinforcement, embankment